Características agronômicas da soja em função do percentual de desfolha em duas cultivares e diferentes estádios fenológicos - Glier, Cláudio Alexandre da Silva (2013)
The aim of this work was to evaluate the agronomic variables due to the effects of different levels of defoliation in vegetative and reproductive phases of two soybean cultivars. The experiment was conducted during the 2011/12 season and the experimental design was a randomized block design with three replications in a factorial 2x4x5, two cultivars were exposed to defoliation in V4, V9, R3 and R5 with percentages 0, 25, 50, 75 and 100%. The cultivar 'NK 7059RR' compared with cv. 'NA 4990RG' had the highest height, the highest number of pods per plant, number of grains per pod, the largest mass of 1,000 grains and therefore the highest yield. The cultivar 'NK7059RR' showed less sensitivity to defoliation than the cultivar 'IN 4990RG'. The number of seeds per pod was affected at the level of 75% and 100% defoliation. The thousand grain weight decreased significantly at stages R3 and R5 at all levels of defoliation. The defoliation of 25% affected the productivity of the cultivar 'IN 4990RG'. The defoliation carried out in stage V4 affected more productivity than at stage V9 environmental conditions of the study. Defoliations held at R5 stage are the most harmful to the crop, reducing the yield potential of soybeans